A multi-criteria trajectory-based parameter sampling strategy for the screening method of elementary effects. (February 2015) - Khare, Y.P.; Muñoz-Carpena, R.; Rooney, R.W.; Martinez, C.J.
Abstract: Environmental models are inherently complex and often characterized by high dimensionality. The method of elementary effects (EE) is one of the most widely used parameter screening technique implemented to reduce burden on computational resources required for thorough model evaluation. Due to issues like inefficient screening and excessive sampling time, the development of more effective EE sampling strategies has been a recent research focus. This paper presents a new sampling strategy - Sampling for Uniformity (SU) – based on the principles of meeting close-to-theoretical parameter distributions and maximizing trajectory spread. The performance of the SU relative to existing strategies was evaluated using a number of criteria including generated parameter distributions' uniformity, time efficiency, trajectory spread, and screening efficiency. The SU performed better than some trajectory-based benchmark strategies across the evaluation criteria, underlining the effectiveness of multi-criteria based sampling and the need to focus future efforts on exploring other combinations of sampling criteria. Highlights: We developed a new parameter sampling strategy for the Morris method of screening. Performance of new strategy was evaluated and compared with benchmark strategies. Evaluation matrix include time, distribution, spread and screening efficiency. New strategy, in general, performed better than existing trajectory-based strategies.